Perlindungan Hukum Data Pribadi Nasabah Dalam Praktik Peer To Peer Lending Syariah Berbasis Teknologi (Perbandingan Hukum Antara Indonesia Dengan Singapura) - Pawestri, Aris Yuni; Ridlo, Muhammad Zainur; Nigtyas, Binaridha Kusuma; Ramadani, Wahyu Ramadani (Universitas Muhammadiyah Jember, 2024)
One form of legal protection for customers is related to confidential information, namely in the filed of customer data protection. Since the implementation of Peer to Peer lending in providing services to customers, the regulation of customer protection in the field of personal daa protection has become something very important to study. The basic policy of Indonesian philosophy relating to this matter is matter is contained in our constitution, namely the Constitution of the Republic of Indonesia in article 34 paragraph (4) which provides the mandate that the Indonesian economy is organized based on economic democracy with the principles of toghetherness, efficiency, justice, sustainability, economic unity.The concept of ideal legal protection of customer personal data information in the future is viewed from a comparison of laws in the two countries. A regulatory formulation regarding the legal protection of customer personal data in Sharia Peer to Peer lending practice, analyzed based on a review of customer legal protection regulations based on banking laws and statutory regulations goversing Sharia Peer To Peer Lending. The urgency of regulating protection for customers in Sharia Peer to Peer lending practices in order to fulfill the state’s obligation in providing protection for citizens, especially protection of personal data of customer using Sharia Peer to Peer Lending, both in Indonesia and Singapore.Keywords : Legal Protection, Sharia Peer to Peer Lending, Customer data.